Latent cytomegalovirus infection and innate immune function following a 75 km cycling time trial - LaVoy, E. C. P.; Nieman, D. C.; Henson, D. A.; Shanely, R. A.; Knab, A. M.; Cialdella-Kam, L.; Simpson, R. J. (European Journal of Applied Physiology, 2013)
Purpose This study compared the acute immune response, inflammation, and lipid peroxidation to a 75 km cycling time trial in male athletes testing positive or negative for latent cytomegalovirus (CMV) infection. Design Trained cyclists (N = 20) were tested for CMV serostatus, and cycled 75 km on a mountainous course using indoor trainers with continuous workload monitoring. Pre-, post-, and 1 h post-exercise blood samples were analyzed for total blood leukocyte counts, blood granulocyte (GR) and monocyte (MO) phagocytosis (PHAG) and oxidative burst activity (OBA), four plasma cytokines, and plasma F2-isoprostanes. Results Forty percent of the subjects tested positive for CMV. No differences in subject characteristics were found between CMVpos and CMVneg groups. Mean power (57.3 ± 1.6, 59.4 ± 1.8 % maximal Watts, p = 0.803), heart rate (87.0 ± 1.0, 86.5 ± 1.3 % maximal heart rate, p = 0.376), and total time (2.56 ± 0.08, 2.60 ± 0.08 h, p = 0.744) to complete the 75 km cycling time trial did not differ between CMVpos and CMVneg groups. Whereas exercise induced significant changes in total blood leukocyte counts, GR and MO-PHAG, four plasma cytokines, and plasma F2-isoprostanes (p < 0.05, w^2 > 0.03), these exercise-induced changes did not differ between CMVpos and CMVneg groups (p > 0.05, w^2 < 0.01). Conclusions CMV serostatus does not appear to influence these innate immune responses or markers of inflammation and lipid peroxidation in response to a single bout of heavy exertion.